Metal Complexes of Biologically Potential Quinazoline Schiff Base - Rajeev Kishore, Kumar; Rai, B.K. (Asian Journal of Chemistry, 2010)
Metal complexes of Co(II), Ni(II) and Cu(II) with Schiff base, 3- amino-2-phenyl-4(3H)- quinazoline semicarbazone (APQS) have been synthesized and characterized by elemental analyses, molar mass, molar conductance, magnetic susceptibility, IR, UV-visible studies. These studies proposed tridentate behaviour of the ligand and coordination takes place through azomethine nitrogen, carbonyl oxygen and secondary amino group of quinazoline side chain. Electronic spectra and magnetic susceptibilities value proposes octahedral geometry for the complex. The molar conductance value indicates complexes were electrolytic in nature of the 1:2 type. The ligand APQS and its metal complexes were also screened for their antibacterial and antifungal activities.